Predicting the Fatigue Failure of Fiber Reinforced Composite Materials Using Artificial Neural Networks - Al Assadi, Mohamed (2009)
A Master of Science Thesis in Mechatronics Submitted by Mohamed Al Assadi Entitled, "Predicting the Fatigue Failure of Fiber Reinforced Composite Materials Using Artificial Neural Networks," September 2009. Available are both Soft and Hard Copies of the Thesis.